Potensi Wisata Olahraga Arung Jeram Di Kecamatan Bonjol Kabupaten Pasaman - Erwin, Erwin Syah Putra; Komaini, Anton; Gemaini, Andri; Syafrianto, Donal (Jurnal IKEOR, 2023)
Abstract: The problem of this study is that the potential of boating sports tourism in Bonjol District, Pasaman Regency is still unknown. The purpose of this study is to determine the potential of boating sports tourism in Bonjol District, Pasaman Regency. The type of research used is qualitative research. The informants for this study were managers, local communities and visitors or tourists. The instrument used in this study was an interview which was then supported by documents. Data were analyzed using the SWOT (Strengths, Weaknesses, Opportunities and Threats) method. Based on the research results obtained: a) The strength of the boating sports tourism potential in Bonjol district lies in its beautiful natural resources (safe, healthy, well-cared for and beautiful) ( SDA) and strategic and quality human resources (HR) and completion of boating equipment in Bonjol District, b) Weak potential for boating sports tourism in Bonjol District including managers/organizations that do not organized, budget constraints, maintenance of tourist attractions and promotion are still lacking The potential for rafting sports tourism in Bonjol district is to create jobs and attract investors. d) Threats to the boating tourism potential in Bonjol district include natural events, development of other tourist attractions and lack of awareness among tourists to Bonjol district. Maintain tourist attractions Keywords : Tourism Potential, Rafting Sports